STUDY OF THE ANTIRADICAL ACTIVITY OF ASIAN MINT (MENTHA ASIATICA) PLANT - Z. K. Oribjonova (Scholars Digest Publishing, 2025)
Plant extract was obtained through ethanol-based ultrasonic extraction and tested at different concentrations (25, 50, 75, and 100 μL) against DPPH radicals. Spectrophotometric measurements were performed at 517 nm to assess the degree of radical neutralization. The results demonstrated that the Mentha asiatica extract possesses significant antiradical potential, with an IC₅₀ value of 93.41 μL, indicating moderate antioxidant activity. These findings confirm the presence of bioactive compounds, particularly natural polyphenols and flavonoids, contributing to the plant’s radical scavenging efficiency. The study provides scientific evidence supporting the traditional use of Mentha asiatica as a natural remedy and highlights its potential for development into pharmaceutical or nutraceutical antioxidant products.
Keywords: Mentha asiatica, Asian mint, antiradical activity, DPPH assay, IC₅₀, spectrophotometry, ethanol extraction, free radicals, polyphenols, natural antioxidants, bioactive compounds.